The Dynamics of Education and Athlete Development: Coaches’ Perceptions of Karate Athletes Studying Outside Their Home Region - Prasetia, Sonia Ider; Barlian, Eri; Setiawan, Yogi; Mardesia, Pringgo (International Martial Arts and Culture Journal, 2024)
Background and Aim. The increasing number of karate athletes pursuing higher education outside their home region has introduced new dynamics in both education and athlete development. Educational mobility offers opportunities for academic growth, independence, and broader life experience, yet it also raises challenges related to training continuity, coach athlete communication, and performance development. In this context, coaches’ perceptions play a crucial role in understanding how athlete development is shaped. This study aims to explore coaches’ perceptions of karate athletes studying outside their home region and to examine the dynamics between education and athlete development.Methods. This study employed a qualitative research approach. Data were collected through in-depth interviews, observations, and documentation involving nine participants, consisting of karate coaches, karate athletes, and sport administrators affiliated with FORKI in Sungai Penuh City. The data were analyzed thematically to identify patterns of perception and coaching experiences related to out-of-region education.Results. The findings indicate that coaches generally perceive studying outside the home region as beneficial for athletes’ academic development, independence, and expanded perspectives. However, coaches also reported challenges in athlete development, particularly limited training supervision, conflicts between academic schedules and training programs, and reduced communication intensity. These conditions were perceived to potentially affect training consistency as well as athletes’ physical and technical development.Conclusion. The study concludes that the relationship between education and athlete development among karate athletes studying outside their home region is dynamic and complex. Adaptive coaching strategies, sustained communication, and flexible training management are essential to support sustainable athlete development amid increasing educational mobility.